Effects of elevated CO2 concentration and experimental warming on morphological, physiological, and biochemical responses of winter wheat under soil water deficiency - Chang, Zhijie; Hao, Lihua; Lu, Yunze; Liu, Liang; Chen, Changhua; Shi, Wei; Li, Yue; Wang, Yanrui; Tian, Yinshuai (Frontiers in Plant Science, 2023)
Global climate change and freshwater scarcity have become two major environmental issues that constrain the sustainable development of the world economy. Climate warming caused by increasing atmospheric CO2 concentration can change global/regional rainfall patterns, leading to uneven global seasonal precipitation distribution and frequent regional extreme drought events, resulting in a drastic reduction of available water resources during the critical crop reproduction period, thus causing many important food-producing regions to face severe water deficiency problems. Understanding the potential processes and mechanisms of crops in response to elevated CO2 concentration and temperature under soil water deficiency may further shed lights on the potential risks of climate change on the primary productivity and grain yield of agriculture. We examined the effects of elevated CO2 concentration (e[CO2]) and temperature (experimental warming) on plant biomass and leaf area, stomatal morphology and distribution, leaf gas exchange and mesophyll anatomy, rubisco activity and gene expression level of winter wheat grown at soil water deficiency with environmental growth chambers. We found that e[CO2] × water × warming sharply reduced plant biomass by 57% and leaf photosynthesis (Pn) 50%, although elevated [CO2] could alleviated the stress from water × warming at the amount of gene expression in RbcL3 (128%) and RbcS2 (215%). At ambient [CO2], the combined stress of warming and water deficiency resulted in a significant decrease in biomass (52%), leaf area (50%), Pn (71%), and Gs (90%) of winter wheat. Furthermore, the total nonstructural carbohydrates were accumulated 10% and 27% and increased Rd by 127% and 99% when subjected to water × warming and e[CO2] × water × warming. These results suggest that water × warming may cause irreversible damage in winter wheat and thus the effect of “CO2 fertilization effect” may be overestimated by the current process-based ecological model.